Project-based organizing and strategic management - Cattani, Gino. (Bingley, U.K. : Emerald, 2011)
This volume is designed to renew, stimulate and facilitate discussion about project-based organizations (PBOs) and how they increasingly pervade business dimensions, from R&D and new product development, to the production of complex capital goods and implementation of organizational change across very different industries such as management consulting, engineering or entertainment. Contributors analyze PBOs as firms, units or networks of firms set up to complete a specific assignment, as well as address the evolution from traditional operations-driven project management, to the strategic role of projects in delivering innovation and organizational change, and the implications for research and teaching. The volume brings together scholars with a diverse theoretical background and using a wealth of methodological approaches in studying PBOs. It focuses on theoretical frameworks for understanding PBOs through different lenses, looks at learning at the individual, team and organizational levels in temporary organizational structures, investigates current issues related to projects and networks, and identifies new areas for future research.
Innovation in complex products and systems : implications for project-based organizing / Andrew Davies, Tim Brady, Andrea Prencipe, Michael Hobday -- Varieties of cooperative strategy in project based organizing : the case of international motion picture co-production / Paul F. Skilton -- Temporary modes of project-based organization within evolving organizational forms : insights from Oticon's experiment with the spaghetti organization / Robert DeFillippi, Mark Lehrer -- Projects, paradigms and predictability / Paul Nightingale, Tim Brady -- Organizational learning implications of partnering flexibility in project-venture settings : a multilevel framework / Andreas Schwab, Anne S. Miner -- Terminating institutionalized termination : why SEMATECH became more than a temporary system / Gordon M$1#7H(Bler-Seitz, J$1'Xr(Bg Sydow -- Project management : learning by violating principles / Vincent Mangematin, Sylvie Blanco, Corine Genet, Bange Deschamps -- Projects, project capabilities and project organizations / Paul Nightingale, Charles Baden-Fuller, Michael M. Hopkins -- Strategy and capabilities in the P-form corporation : linking strategic direction with organizational capabilities / Jonas S$1)36(Berlund, Fredrik Tell -- Strategic responses to standardization : embrace, extend or extinguish? / C. Jason Woodard, Joel West -- Shared leadership functions in geographically dispersed project teams / Miriam Muethel, Martin Hoegl -- Staying local or reaching globally? : analyzing structural characteristics of project-based networks in German biotech / Andreas Al-Laham, Terry L. Amburgey -- A model of and for virtual projects / Raghu Garud, Arun Kumaraswamy, Philipp Tuertscher -- Reconsidering ambidexterity at the individual level : a social network perspective / Fanny Simon, Albic Tellier -- Toward a projects as events perspective / Massimo Maoret, Felipe G. Massa, Candace Jones -- Institutional dynamics of project-based creative organizations : Irving Thalberg and the Hollywood Studio System / Joseph Lampel -- Temporary identities : hybridity and the construction of identities in the U.S. feature film industry / Fabrizio Perretti -- Projects of passion : lessons for strategy from temporary art / Silviya Svejenova, Jesper Strandgaard Pedersen, Luis Vives.s
Keywords: Strategic planning; Project management